Drop the ball : achieving more by doing less - Dufu, Tiffany (Flatiron Books, 2017)
"A renowned expert in the women's leadership movement, Tiffany Dufu was once like so many other driven and talented women who have been brought up to believe that to have it all, they must do it all. But after she gave birth to her first child, she struggled to accomplish everything she thought she needed to in order to succeed. Dufu began to feel that achieving her career and personal goals was an impossibility. Eventually, she discovered the solution: letting go. In Drop the Ball, Dufu recounts how she learned to reevaluate expectations, shrink her to-do list, and meaningfully engage the assistance of others--freeing the space she needed to flourish at work and to develop deeper, more meaningful relationships at home. Even though women make up half the workforce, they still represent only 18 percent of the highest-level leaders. The reasons are obvious: just as women reach middle management, they are also starting families. Mounting responsibilities at work and home leave them with no bandwidth to do what will most lead to their success. Offering new perspective on why the women's leadership movement has stalled, and packed with actionable advice, Tiffany Dufu's Drop the Ball urges women to embrace imperfection and to expect less of themselves and more from others--only then can they focus on what they truly care about, devote the necessary energy to achieving their real goals, and create the type of rich, rewarding lives we all desire."--Dust jacket.